Mediator Role of Organizational Commitment to Performance - Nurluviyana, Nurluviyana; Sudarma, Ketut (Management Analysis Journal, 2020)
The aims of this study is to determaine the effect of spiritual leadership (X1) and quality of work life (X2) on performance (Y2) with organizational commitment (Y1) as a mediation on employees of Wimarion Hotel Semarang. The type and design of the research used in this study is quantitative research. Sampling in this study using a saturated sampling system and obtained the sample size that must be used is 70 employees. The analytical method used is the test instrument (validity and reliability), classic assumption test, and hypothesis testing with IBM SPSS Verse 23 and mediation testing with Sobel test. Application methods of data collection using interviews, quetionnares, and literature studies. The result of this study show that all of seven hypotheses were accepted. Therefore could be known that spiritual leadership has a positive and significant effect on organizational commitment. Quality of work life has a positive and significant effect on organizational commitment. Spiritual leadership has a positive and significant effect on performance. Quality of work life has a positive dan significant effect on performance. Organizational commitment has a positive dan significant effect on performance. Organizational commitment is able to mediate the relationship between spiritual leadership and performance. And organizational commitment is able to mediate the relationship between quality of work life and performance.